A Reappraisal on Marketing Definition and Marketing Theory - Liu, Ran (Journal of Eastern European and Central Asian Research (JEECAR), 2017)
This study examines the definition of marketing and different marketing theories for academic research based on historical literature review. After a comprehensive review on different approaches on marketing definition, the paper gives its own description of marketing, with a highlight on value creation and exchange. The paper also attempts to discuss the possibility that a potential new paradigm of marketing as a science by a value creation theory, which focus on the new role of marketing in value creation during the traditional transaction exchange, with a suggestion that the impact of marketing maybe underestimated.